2020
DOI: 10.1016/j.jtcme.2020.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Obesity preventive function of novel edible mushroom, Basidiomycetes-X (Echigoshirayukidake): Manipulations of insulin resistance and lipid metabolism

Abstract: s Echigoshirayukidake is an edible mushroom found in Uonuma, Japan in 1994. It was assigned to a new species of Basidiomycetes (BDM-X) but is uniquely defect of forming bashidium. The high antioxidant activity and β-glucan content of BDM-X suggest possible functions preventing type 2 diabetes. In the present study, anti-obesity and insulin resistance preventive functions of BDM-X were examined using genetically defined obese model rat, OLETF (Otsuka Long Evans Tokushima Fatty)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…The present finding that the formyl pyrrole alkaloids are present in Basidiomycetes-X, therefore, supports the idea that these pyrrole alkaloids are playing crucial roles in the observed medicinal and pharmacological functions of this mushroom so far, we reported elsewhere [ 3 , 4 , 5 , 6 , 7 ]. Especially, the finding of amide analogue (compound II) as the novel ingredient of Bashidiomycetes -X provided a new insight to the functions of this mushroom because the amide structure, which is rather stable, will differentiate the metabolic behaviors from the acid homologue (compound I), and, thus, a discussion will be expanded if they have similar functions or some new functions are involved in the amide analogue.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present finding that the formyl pyrrole alkaloids are present in Basidiomycetes-X, therefore, supports the idea that these pyrrole alkaloids are playing crucial roles in the observed medicinal and pharmacological functions of this mushroom so far, we reported elsewhere [ 3 , 4 , 5 , 6 , 7 ]. Especially, the finding of amide analogue (compound II) as the novel ingredient of Bashidiomycetes -X provided a new insight to the functions of this mushroom because the amide structure, which is rather stable, will differentiate the metabolic behaviors from the acid homologue (compound I), and, thus, a discussion will be expanded if they have similar functions or some new functions are involved in the amide analogue.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that the aqueous extract of Basidiomycetes - X showed a potential hydroxylradical scavenging activity and protective effects on lipopolysaccharide-induced hepatic oxidative damage in mice [ 3 ]. Further studies revealed that Basidiomycetes-X has potential anti-obesity and hepatoprotective functions in rodents [ 4 , 5 ], and it inhibits atopic dermatitis in a mouse model [ 6 ]. Quite recently, Basidiomycetes - X was also reported to prevent and ameliorate non-alcoholic steatohepatitis (NASH) in fatty liver model rats [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…So far, several animal and human studies on the medicinal functions of BDM-X have been carried out and are summarized in Table 2; these include antioxidant protection [68], anti-obesity effects [69,70], hepatoprotective functions [69,71,72] and immune modulation, including the ameliorative effect on atopic dermatitis [73,74]. It is worth discussing the possible contribution of identified BDM-X components to those already known, as well as other unpublished functions.…”
Section: Medicinal and Pharmacological Functions Of Bdm-x Contributin...mentioning
confidence: 99%
“…This observation is consistent with the recent study of Sheng et al [37], who reported that water extract from mushroom Pleurotus citrinopileatus significantly decreased the food intake resulting to the reduction of weight gain and fat accumulation in highfat diet-fed C57BL/6J mice. In addition, Khatun et al [38] reported that feeding of edible mushroom Echigoshirayukidake supplemented chow (5% w/w) significantly reduced the food intake and prevented body weight gain, fat deposition in the viscera, and hyperlipidemia in genetically defined obese model rat.…”
Section: In-vitro Activity Of L Strigosus Mycelial Extract In C Elementioning
confidence: 99%